Chronic Caffeine Treatment Protects Against α-Synucleinopathy by Reestablishing Autophagy Activity in the Mouse Striatum - Luan, Yanan; Ren, Xiangpeng; Zheng, Wu; Zeng, Zhenhai; Guo, Yingzi; Hou, Zhidong; Guo, Wei; Chen, Xingjun; Li, Fei; Chen, Jiang-Fan (Frontiers in Neuroscience, 2018)
02-18-2018 resubmitted to Frontier in Neuroscience Chronic caffeine treatment protects against α-synucleinopathy by reestablishing autophagy activity in the mouse striatum Yanan Luan &1, Xiangpeng Ren#&1,2, Wu Zheng1,2, Zhenhai Zeng1, Yingzi Guo1, Yuling Zhou1, Zhidong Hou1, Wei Guo1,2, Jiang-Fan Chen #1,2,3 1Molecular Neuropharmacology Laboratory, School of Optometry and Ophthalmology and Eye Hospital, Wenzhou Medical University, Wenzhou, Zhejiang, China; 2State Key Laboratory of Optometry & Vision Science, Wenzhou, Zhejiang, China; 3Department of Neurology, Boston University School of Medicine, Boston, Massachusetts &These authors contributed to this work equally. #Corresponding Authors: Jiang-Fan Chen (chenjf555@gmail.com), Xiangpeng Ren (renxpeng@mail3.sysu.edu.cn) Keywords: α-synuclein; caffeine; autophagy; macroautophagy; α-synucleinopathy; Parkinson’s disease; striatum. Abstract Despite converging epidemiological evidence for the inverse relationship of regular caffeine consumption and risk of developing Parkinson’s disease (PD) with animal studies demonstrating protective effect of caffeine in various neurotoxin models of PD, whether caffeine can protect against mutant α-synuclein (α-Syn) A53T-induced neurotoxicity in intact animals has not been examined. Here, we determined the effect of chronic caffeine treatment using the α-Syn fibril model of PD by intra-striatal injection of preformed A53T α-Syn fibrils. We demonstrated that chronic caffeine treatment blunted a cascade of pathological events leading to α-synucleinopathy, including pSer129α-Syn-rich aggregates, apoptotic neuronal cell death, microglia and astroglia reactivation. Importantly, chronic caffeine treatment did not affect autophagy processes in the normal striatum, but selectively reversed α-Syn-induced defects in macroautophagy (by enhancing microtubule-associated protein 1 light chain 3, and reducing the receptor protein sequestosome 1, SQSTM1/p62) and chaperone-mediated autophagy (CMA, by enhancing LAMP2A). These findings support that caffeine―a strongly protective environment factor as suggested by epidemiological evidence―may represent a novel pharmacological therapy for PD by targeting autophagy pathway. Introduction Parkinson’s disease (PD) is pathologically characterized by selective degeneration of dopaminergic neurons in the midbrain and the presence of intracellular amyloidogenicα-synuclein (α-Syn) inclusions, known as Lewy bodies and Lewy neurites, which progress from the medulla to midbrain and throughout cortical areas. The studies over the last two decades have identified altered α-Syn function as a key molecular pathogenesis mechanism of PD (Goedert, 2001; Lashuel et al., 2013; Wong and Krainc, 2017). Many recent studies also suggested a “prion-like”